PENGEMBANGAN MULTIMEDIA INTERAKTIF MENGGUNAKAN CAMTASIA STUDIO 8 PADA PEMBELAJARAN BIOLOGI MATERI KULTUR JARINGAN UNTUK SISWA SMA KELAS XI MIA - Nabella winanda aulia; Mia Aina (Program Studi Pendidikan Biologi FKIP Universitas Jambi, 2016)
ABSTRACT. This research purpose is to develop multimedia learning in plant tissue isolation method. This kind of research is development research which using ADDIE development model. Before trials, this multimedia has been validated by media and material expert. Multimedia learning trials to a small group in 3 classes in SMA N 1 Kota Jambi. The media validation result, conducted in 2 stages with the final score 96% with it means very good category. The material validation result conducted in 3 stages with the final result 80% which is very good category. The result of small group trials XII MIA 1 the result is 92% , in XII MIA 2 the result is 92%, in XII MIA 4 the result is 91,33% with very good Category. Over all the conclusion is tthe development of multimedia is very good category, interesting and enable to use as multimedia learning of plant tissue isolation method . Keyword : interactive multimedia , camtasia studio 8 , plant tissue isolation method